Implementasi Akuntabilitas Berbasis Nilai Amanah Dalam Pengelolaan Dana Titipan Santri Untuk Simpanan Wajib: Studi Kasus Pondok Pesantren Sabilul Huda Warrosyad - Cep Subhan; Laras Pratiwi (Mazinda : Jurnal Akuntansi, Keuangan, dan Bisnis, 2026)
Islamic boarding schools (pesantren) bear broad responsibility for managing funds entrusted by students’ parents, including monthly deposits allocated for compulsory savings. Managing these funds requires accountability that is not merely administrative but also carries moral and spiritual dimensions reflected in the value of amanah (trustworthiness). This study analyzes the implementation of amanah-based accountability in managing student deposit funds for compulsory savings at Pondok Pesantren Sabilul Huda Warrosyad. A descriptive qualitative approach with a case study design was employed. Data were collected through in-depth interviews with six purposively selected informants — the pesantren caretaker, fund manager, financial administration staff, school committee member, a student, and a parent/guardian — supplemented by observation and documentation. Data were analyzed using staged coding consisting of open, axial, and selective coding, with credibility ensured through source, method, and time triangulation. The findings reveal three main themes: fund management that still relies on manual bookkeeping, reporting transparency that remains reactive toward parents, and amanah-based accountability that has been strongly internalized on the moral-spiritual dimension but not yet matched by stronger administrative systems. The study concludes that amanah-based accountability at the pesantren is morally sound but requires strengthening of recording and reporting systems so that accountability becomes comprehensive in both spiritual and administrative terms.